IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PEMBERDAYAAN MASYARAKAT DALAM MEMPERTAHANKAN CITRA PERUSAHAAN PADA PT PUPUK KALTIM - Rifadin Noor; Yunus Tulak Tandirerung; Andi Arfina Padri Hasanah (Politeknik Negeri Samarinda, 2020)
The aim of the study was to know how much the implementation of the Corporate Social Responsibility program had a positive impact on PT Pupuk Kaltim image in the education sector. The results of this study indicate that the Corporate Social Responsibility program undertaken by PT Pupuk Kaltim received a positive response on the stakeholders. This is evidenced by the results of the environmental satisfaction survey which reached 88% and the examinations conducted by researchers regarding the effect of Corporate Social Responsibility programs on PT Pupuk Kaltim image were 54.9%. Also already had gold proper for two consecutive in years, the CSR program can maintain the image of PT Pupuk Kaltim on the stakeholders. Keywords: CSR, Education, Community Empowerment, Gold Proper